Body composition, psychological, cardiovascular and physical activity factors related with academic school performance (2021)
The aim of the present study was to analyse body composition, anxiety, cardiovascular, and physical activity factors related with academic performance of school students as well as to analyse differences, by age, in these factors. We analysed in 266 primary school students’ (8.81 ± 1.62 years, range: 5–13 years) heart rate, anthropometric variables to calculate body mass index, physical activity performance, anxiety levels and academic results by the average of marks. Students were divided in two different groups, firstly by their lower or higher academic performance, and secondly by age. Results showed a negative correlation between academic performance and age, weight, body mass index and trait anxiety variables. Additionally, significant differences were found by age, presenting older students higher scores in body mass index and lower physical activity, trait anxiety, heart rate and academic performance values than younger students. Overweight and obesity may have a greatimpact in academic performance in children and we pointed out the necessity to establish programs related with healthy habits which include improvements in physical activity and nutrition behaviours with the objective to enhance children’s health general status, psychological profile, cognitive and motor development, and academic performance.